The Socialization of Breathing Muscle Stratching Therapy on Increasing Vital Lung Capacity of Theasthma at Grandmed Hospital Lubuk Pakam - Wati, Syatria; Hijriana, Isni; Simarmata, Juni Mariati; Pitriani, Pitriani (JURNAL PENGMAS KESTRA (JPK), 2023)
Asthma is a disease of shortness of breath due to the narrowing of flight routes. A decrease in the expiratory rate and inspiratory volume lowers the lung fundamentals. Asthmatic patients need exercise to expand the lung boundaries which is very necessary. Respiratory muscle stretching exercises are activities to maintain and build the adaptability or adaptability of the respiratory muscles. This examination aims to determine the impact of prolonged treatment on the respiratory muscles to establish the lung margins that are important for asthmatic patients. This PkM activity is carried out through outreach activities combined with demonstration and discussion methods. The PkM activity begins with the provision of pre-test questions and ends with a post-test to measure the increase in PkM participants' knowledge of the socialized material. This PkM activity has been carried out very well where as many as 17 PkM participants who are nurses at Grandmed Lubuk Pakam Hospital have understood the socialization material presented, namely respiratory muscle stretching therapy to increase the lung vital capacity of asthma patients. After the intervention was given, the lung vital capacity of asthma patients changed to be in the good and very good categories. The knowledge and insights of the PkM participants increased with the demonstrations and discussions given. In addition, there was an increase in the knowledge of PkM participants regarding respiratory muscle stretching therapy in asthma patients with an average percent increase of 20%.